Bias-Policy Iteration-Based Adaptive Dynamic Programming for Optimal Control of Discrete-Time Nonlinear Systems - Jiang, Huaiyuan; Li, Xiang; Zhou, Bin; Cao, Xibin (IEEE transactions on circuits and systems. I, Regular papers, 2025)
This paper presents the bias-policy iteration, a modified adaptive dynamic programming method, to achieve optimal control design of discrete-time nonlinear systems. Firstly, the formulation of the bias-policy iteration method and the thorough convergence analysis are provided. By leveraging the bias parameter, the constraint of admissible control is relaxed while the fast convergence of traditional policy iteration is inherited. The actor-critic framework is utilized to realize the implementation of the proposed method accordingly. Finally, the proposed method is applied to optimal control problem of the inverted pendulum system. The simulation is conducted to verify the effectiveness of the bias-policy iteration approach.